2015
DOI: 10.3109/14767058.2015.1018821
|View full text |Cite
|
Sign up to set email alerts
|

Crack abuse during pregnancy: maternal, fetal and neonatal complication

Abstract: Crack abuse had significant influence on pregnancy outcomes. Crack appears to influence the prevalence of low birth weight, preterm labor, preeclampsia and placental abruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 22 publications
2
20
0
13
Order By: Relevance
“…A similar report had been made by Aghamohammadiet al [18] in Iran. Tebeuet al [19], in Yaoundé, had also noticed that the aged primiparouswas associated to a strong rate of caesarean section.…”
Section: Age Of the Parturient And Mode Of Childbirthsupporting
confidence: 84%
“…A similar report had been made by Aghamohammadiet al [18] in Iran. Tebeuet al [19], in Yaoundé, had also noticed that the aged primiparouswas associated to a strong rate of caesarean section.…”
Section: Age Of the Parturient And Mode Of Childbirthsupporting
confidence: 84%
“…The results show innumerous negative outcomes for newborn health. Concerning the common physiological outcomes, low birth weight (Aghamohammadi & Zafari, 2016;Bateman, Ng, Hansen, & Heagarty, 1993;Behnke et al, 2001;Bender et al, 1995;R Cherukuri, Minkoff, Feldman, A, & Glass, 1988;Radha Cherukuri, Howard, Parekh, Feldman, & Glass, 1987;Fiocchi & Kingree, 2001;Leblanc, 1987;Mardini et al, 2016Mardini et al, , 2017Parcianello et al, 2018;Sprauve, Lindsay Michael K., Herbert, & Graves, 1997;Zavaschi et al, 2014) preterm delivery (Aghamohammadi & Zafari, 2016;Bateman et al, 1993;Behnke et al, 2001;R Cherukuri et al, 1988;Radha Cherukuri et al, 1987;Eyler et al, 1998;Fiocchi & Kingree, 2001;Leblanc, 1987;Reis & Loureiro, 2015;Sprauve et al, 1997;Xavier et al, 2017) and small for gestational age (Behnke et al, 2001;Leblanc, 1987;Reis & Loureiro, 2015) were well establish risk between newborn exposure to crack cocaine during pregnancy (dos Santos et al, 2018). The low 5-minute Apgar score (Parcianello et al, 2018;Sprauve et al, 1997) and small head circunference (Behnke et al, 2001;R Cherukuri et al, 1988;Radha Cherukuri et al, 1987;Leblanc, 1987) were also reported as a risk to crack cocaine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The most common outcomes in children exposure to crack cocaine were preterm delivery, low birth weight, small for gestational age and small head circumference, when compared with the drug-free groups. These outcomes were possibly associated with nutrition problems during pregnancy, due to the gradual reduction in placental blood flow produced by vasoconstriction, decreasing oxygen and nutrient transfer to the fetus (Aghamohammadi & Zafari, 2016) and complications in brain development (McCarthy, Kabir, Bhide, & Kosofsky, 2014;Nordstrom-Klee, Delaney-Black, Covington, Ager, & Sokol, 2002). Also, it is important that pregnant crack cocaine users usually present inadequate nutrition intake (Eide, Stevens, Schuetze, & Dombkowsko, 2006;Fajemirokun-Odudeyi & Lindow, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are around 750,000 cocaine-exposed pregnancies every year (Cain, Bornick, & Whiteman, 2013). The consequences of prenatal cocaine exposure include negative pregnancy outcomes, such as higher rates of preeclampsia, placental abruption, preterm labor, and low birth weight, and abnormal neuron morphology, behavior problems, and cognitive deficits in memory in prenatally exposed offspring (Ackerman, Riggins, & Black, 2010;Aghamohammadi & Zafari, 2016;Cutler, Wilkerson, Gingras, & Levin, 1996;Lu, Liu, Long, & Ma, 2012). Some of the consequences of prenatal cocaine exposure may be mediated by miR-212, which has been found to be induced by cocaine in the dorsal striatum of rats where it amplifies cAMP response element binding protein signaling (Hollander et al, 2010).…”
Section: Cocainementioning
confidence: 99%